Precise velocity control of a bipedal robot using CPG circuits in creating different behaviors*. (1st October 2016) - Komatsu, Tadashi; Saito, Kengo
Abstract: In this paper, we have extended our previous work, which created several motion phases in running and walking movements with a central pattern generator (CPG) model, to controlling the robot's walking speed easily and precisely within a wide speed range to investigate the possibility of CPG in the domain of bipedal robotic locomotion. Our method proposed herein basically used our hybrid CPG (H-CPG) model. This model consisted of a rhythm generator using CPG, a force controller, and an attitude controller. We have also introduced a modulation mechanism using a velocity feedback loop in this force controller for the precise control of acting forces from the tip of the support leg to the floor and the walking stride length. This mechanism can realize accurate modulation of the walking velocity reflecting an error between the target velocity and the current velocity in real time. Numerical simulation results show the effectiveness of the proposed method for realizing precise control of the locomotion speed in both backward and forward stable walking.